Study on the Translation of Chinese Chic Brands from the Perspective of Domestication and Foreignization: A Case Study of CHAGEE - Tian, Yuanyuan; Sun, Jiameng (International Journal of Social Sciences and Public Administration, 2024)
In the wave of globalization, the strategy of Chinese chic brands going abroad has increasingly become an important way to enhance international influence. The study employs a mixed-method approach, combining practical case study analysis with quantitative data on market performance. By scrutinizing CHAGEE’s translation practices across various product lines and marketing materials, this research identifies common pitfalls in Chinese brand translation, including over-reliance on literal translation, cultural disconnect and insufficient adaptation to target markets. The findings reveal that successful brand internationalization requires a nuanced approach to translation, one that harmonizes cultural sensitivity with brand essence. This paper proposes effective translation strategies tailored to Chinese chic brands, offering practical guidelines for establishing distinctive brand images in international markets while maximizing both cultural dissemination and commercial value.